Puig Adam and the Instituto-Escuela of Madrid - Carrillo-Gallego, Dolores; Dólera-Almaida, Josefa; Sánchez-Jiménez, Encarna (Historia y Memoria de la Educación, 2024)
The professor of mathematics at the San Isidro secondary school in Madrid, Pedro Puig Adam (1900-1960), was one of the leading figures in mathematics education in Spain; his proposals on this subject were valued nationally and internationally (he was a member of the International Commission for the Study and Improvement of Mathematics Education - CIEAEM and organised its 11th meeting in Madrid). He obtained his PhD in mathematics linked to the Laboratorio y Seminario Matemático, which depended on the Junta para la Ampliación de Estudios (JAE), as well as another secondary school, the Instituto-Escuela de Madrid. Our research studies the influences that Puig Adam received in his proposals on mathematics education, which were influenced by the ideology and practices of the Institución Libre de Enseñanza (ILE) and the Instituto Escuela. Therefore, the aim of this paper is to compare Puig Adam's proposals for the teaching of mathematics with those of the Instituto-Escuela, insofar as both general aspects of mathematics education and the training of mathematics teachers. For this purpose, we have used the decrees of creation of the Instituto-Escuela and the memoirs it produced, contrasting them with Puig Adam's publications on mathematics education between 1926 and 1960.